Measurement of prompt open-charm production cross sections in proton-proton collisions at √s = 13 TeV - CMS Collaboration; Damarseçkin, Serdal (Springer, 2021)
Abstract: The production cross sections for prompt open-charm mesons in proton-proton collisions at a center-of-mass energy of 13 TeV are reported. The measurement is performed using a data sample collected by the CMS experiment corresponding to an integrated luminosity of 29 nb−1 . The differential production cross sections of the D∗±, D± , and D0 (D 0 ) mesons are presented in ranges of transverse momentum and pseudorapidity 4 < pT < 100 GeV and |η| < 2.1, respectively. The results are compared to several theoretical calculations and to previous measurements.
Keywords: B physics; Charm physics; Hadron-Hadron scattering (experiments)